Capicua regulates neural stem cell proliferation and lineage specification through control of Ets factors - Shiekh Tanveer Ahmad (Nature Portfolio, 2019)
Although Capicua (Cic), a transcriptional repressor, is linked to cancer, little is known about its function in the non-diseased brain. Here, authors show that Cic is strongly expressed in astrocytic and neuronal lineage cells during development and regulates proliferation and lineage selection via de-repression of Ets transcription factors.